THE INFLUENCE OF WORK ENVIRONMENT, SPIRITUAL LEADERSHIP AND WORK ETHIC ON EMPLOYEE PERFORMANCE IN THE CIVIL SERVANTS AND WILAYATUL HISBAH POLICE UNIT ACEH TAMIANG REGENCY - Adelia Irma Suryani; Marbawi; Nurfaliza; Ibrahim Qamarius (RADJA PUBLIKA, 2024)
This study aims to analyze the Influence of Work Environment, Spiritual Leadership and Work Ethic on Employee Performance in the Pamong Praja and Wilayatul Hisbah Police Units of Aceh Taming Regency, the dependent variables of this study are work environment, spiritual leadership and Work Ethic for the independent variable is employee performance. The population in this study is 65 employees of the Office of the Pamong Praja and Wilayatul Hisbah Police Unit of Aceh Taming Regency. The technique of sampling saturation or census and a sample of 65 respondents who are employees of the Pamong Praja and Wilayatul Hisbah Police Unit of Aceh Taming Regency, the research method used is a quantitative method, for the data analysis method using multiple regression analysis. The results of this study show that the work environment and work ethic have a significant effect on employee performance, while spiritual leadership does not have a significant effect on employee performance in the Pamong Praja and Wilayatul Hisbah Police Units of Aceh Taming Regency. This study shows that the work environment is the most dominant variable affecting the performance of Office employees at the Pamong Praja and Wilayatul Hisbah Police Units of Aceh Taming Regency. In this study, the work environment and work ethic have a significant effect on employee performance in the Pamong Praja and Wilayatul Hisbah Police Units of Aceh Regency